A calendar method of collecting remittance use data in a remittance dependent setting of Nepal*. (4th May 2017) - Bhandari, Prem; Chaudhary, Indra
Abstract : This methodological paper describes the design and refinement of a calendar method of collecting data on remittance receipt and remittance use and its piloting in a rural remittance dependent setting of Nepal. Much of the previous national surveys collected remittance receipt and remittance use cross-sectional data that used a time frame ranging from 12 to 24 months. These surveys collected remittance receipt data by asking, 'How much money has he/she sent in the past 12 months or 2 years?' We believe that the long time frame of one to two years adds burden to respondents for unnecessary calculations and is prone to re-call bias. Moreover, these surveys used vague words such as 'capital formation' or 'daily consumption' to measure the uses of remittances. Thus, the instrument perse is unreliable posing threats to collecting valid responses. Considering these flaws, in 2013, we designed a calendar with shorter timing cues and simple words for collecting longitudinal data on remittance receipt and remittance use. First, we describe the calendar design process. Next, we provide descriptive results of household responses on the amount of remittance received and the remittance used on various socio-economic and cultural dimensions of household activities. The implications of the insights gained from this study are discussed.